2006
DOI: 10.5194/angeo-24-1581-2006
|View full text |Cite
|
Sign up to set email alerts
|

Observations of GPS ionospheric scintillations over Wuhan during geomagnetic storms

Abstract: Abstract. During the two geomagnetic storms which occurred on 1 October 2002 and 22 January 2004, the strong ionospheric scintillations of the GPS L1 band were observed at Wuhan station (30.6 • N, 114.4 • E, 45.8 • Dip), which is situated near the northern crest of the equatorial ionosphere anomaly. We found that the intense scintillations were associated with the main phases of the storms and were colocated with the enhancement of the equatorial ionization anomaly (EIA); the co-existence of large-and small-sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 38 publications
(23 reference statements)
1
14
0
Order By: Relevance
“…It is known that, besides TIDs, ionospheric irregularities in EIA region can also cause variations in electron density and thus influence the propagation of LSTIDs. However, in the present study, we calculated the rate of TEC index (ROTI), and found that no ionospheric irregularities occurred between 1500 and 1600 UT in South China, although such irregularities were previously observed there during storms [ Li et al , 2006, 2009].…”
Section: Discussionmentioning
confidence: 51%
“…It is known that, besides TIDs, ionospheric irregularities in EIA region can also cause variations in electron density and thus influence the propagation of LSTIDs. However, in the present study, we calculated the rate of TEC index (ROTI), and found that no ionospheric irregularities occurred between 1500 and 1600 UT in South China, although such irregularities were previously observed there during storms [ Li et al , 2006, 2009].…”
Section: Discussionmentioning
confidence: 51%
“…Recently, the GPS ionospheric scintillations at a low-middle latitude station Wuhan in China during storms were studied (Li et al, 2006;Xu et al, 2006Xu et al, , 2007. In the present study, GPS scintillation/TEC measurements at Sanya (18.31N, 109.51E), Digisonde and DMSP plasma density data from other longitude sectors are utilized to study the effects of geomagnetic storms on equatorial ionospheric scintillations during the low scintillation occurrence season (for station Sanya, the GPS ionospheric scintillations mainly occur during equinoctial months (3,4,9,10), and are rarely observed at solstice).…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, in the categories I and II, occurrence of Es layer at the low-latitude station at Hyderabad and equatorial spread-F occurrence at the Tirunelveli in the recovery phases of storms show the anticorrelation. Li et al (2006) suggested that Es layers at low latitude caused inhibition of GPS L-band scintillations on the two of the storms they have investigated. The presence of Es layer in the evening hour can modify the longitudinal/local time gradient in the E-region integrated Pederson conductivity that can affect the intensity of PRE development (Carrasco et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, a total of 73 moderate to intense geomagnetic storm events are identified and classified them into three categories according to Aarons (1991) criteria, which is commonly accepted criteria to explore the occurrence of ionospheric irregularities. It is believed that low-latitude Es layers may be modified due to modified winds/electric fields during the geomagnetic storms, and hence, examining their role in the generation of ESF irregularities is very important (e.g., Li et al, 2006;Sripathi et al, 2018). (2) Category II: if the maximum negative of Dst occurs during the midnight-down (at 00:00-06:00 LT), the height of the ionospheric F layer first rises and then falls, which generated the ionospheric irregularities.…”
Section: Introductionmentioning
confidence: 99%